Akira and the Tokyo Olympics in 1964 and 2020/21: Reading the games through manga and anime—reading manga and anime through the games. Issue 1 (2nd January 2023) - Tagsold, Christian
ABSTRACT: When the manga series Akira appeared in 1982, it quickly became a bestseller, and the 1988 anime version strongly reinforced its popularity. Ōtomo Katsuhiro depicted the dark cityscape of Neo-Tokyo compellingly. However, until now, interpretations mainly focussed on Akira as a prime example of the cyberpunk genre. Yet, the story also revolves around the preparations for a renewed Olympics, celebrating the rebirth of Tokyo. By referencing the 1964 Games, Ōtomo paints a highly critical image of the first Tokyo Olympics, reflecting the mood of the early 1980s, when citizens vehemently opposed plans to host the Olympics in Nagoya. Ōtomo primarily employs some of the 1964 architecture to link Akira to the first Tokyo Olympics. For example, the Temple of Lady Miyako replicates Tange Kenzō's National Gymnasia next to the Meiji Shrine. Together with the new venue for the ( Akira ) Olympics in 2020, the Temple is one of the main action scenes, indicating that a spatial reading of the manga can yield fresh interpretations. Nevertheless, Akira 's critical stance toward the Olympics did not prevent Ōtomo from contributing to the original plan for the 2020 Olympic opening ceremony, which featured characters from Akira to harness its popularity for the global Cool Japan factor. For these reasons, analyzing Akira' s various Olympic dimensions help us better understand Japan's entanglement with this sports mega-event over the last decades. At the same time, a thorough Olympic reading of Akira is long overdue.